A Study of Entanglement and Squeezing of (Journal of Sciences, Islamic Republic of Iran)
We study entanglement and squeezing of a cluster of spin systems under the influence of the two-axis countertwisting Hamiltonian. The squeezing parameters given by Wineland et al and also by Kitagawa et al. are chosen as the criteria of spin squeezing. The criterion of pairwise entanglement is chosen to be the concurrence and that of the bipartite entanglement the linear entropy. We also define a new squeezing parameter ?, which plays a direct role in the investigation of the relationship between squeezing and entanglement. We observe that if the system is squeezed according to the Wineland’s criterion, it is squeezed according to the Kitagawa’s also, but the reverse is not always true. Moreover, if the system is squeezed according to Kitagawa’s criterion, it is pairwise entangled simultaneously and vice versa. It is also observed that the entropy is a linear function of the parameter ?2.